Thyroid‐associated genetic polymorphisms in relation to breast cancer risk in the Malmö Diet and Cancer Study. Issue 7 (29th November 2017) - Brandt, Jasmine; Borgquist, Signe; Almgren, Peter; Försti, Asta; Huss, Linnea; Melander, Olle; Manjer, Jonas
Abstract : Previous studies have suggested that thyroid function is associated with breast cancer risk, which could have an important clinical impact, as one in eight women will develop a thyroid disorder during her lifetime. However, the underlying pathomechanism behind the association is still unknown. We used the Malmö Diet and Cancer Study (a population‐based prospective study consisting of 17, 035 women) to examine 17 single nucleotide polymorphisms (SNPs) previously related to levels of free thyroxine (free T4) and thyroid peroxidase antibodies (TPO‐Ab) as potential genetic risk factors for breast cancer. A baseline examination including free T4 and TPO‐Ab levels was conducted at the time of inclusion. Genotyping was performed on 901 breast cancer patients and 3335 controls. Odds ratios (95% confidence intervals) for high free T4, TPO‐Ab positivity, and breast cancer were calculated by logistic regression and adjusted for confounders. We identified one free T4‐related SNP (rs2235544, D101 gene) that was significantly associated with both free T4 level and breast cancer risk. There was a suggested association between rs11675434 (TPO gene) and TPO‐Ab level, and TPO‐Ab‐related rs11675434 (TPO), rs3094228 (HCP5), rs1033662 (no registered gene), and rs301806 (RERE) were associated with breast cancer risk. There was an indicated interaction between rs6485050 (no registered gene) and free T4 level in regards to breast cancer risk. This is the first study to suggest an association between thyroid‐related SNPs and breast cancer risk. All SNPs have a biological plausibility of being associated with breast cancer risk, and may contribute to the genetic predisposition to breast cancer. Abstract : What's new? Thyroid function is potentially associated with breast cancer risk, a disease for which a significant proportion of genetic susceptibility remains unknown. Here, genetic markers for thyroid hormone and thyroid peroxidase antibody levels were used to investigate potential associations between thyroid function and breast cancer risk. Several single nucleotide polymorphisms (SNPs), located near genes related to thyroid and immune function, were associated with breast cancer risk. Among the identified SNPs was rs2235544 ( D101 gene), a variant associated with free thyroxine levels and breast cancer risk. The findings warrant further exploration to help clarify links between thyroid function and breast cancer.